Study of the Sensitivity of Capsicum Annuum to Increased Salinity Due to Climate Change; [Estudio de la Sensibilidad de Capsicum Annuum Al Aumento de la Salinidad Debido Al Cambio Climático] - Martinez-Salinas, J (Instituto de Botanica del Nordeste, 2025)
Capsicum anuum “pepper” is a vegetable of nutritional importance due to the presence of vitamins, minerals and its organoleptic properties. The main producing areas in Peru are La Libertad, Lambayeque and Piura, where more than 50% of the national production is concentrated. However, one of the main problems for its cultivation is salinity, therefore, the objective of this research was to determine the sensitivity of pepper to increased salinity. The experimental phase was carried out in the Biotechnology Laboratory of the National University of Trujillo, where cell suspensions were grown from calluses, using increasing concentrations of NaCl (0, 25, 50, 75, 100, 200 and 400 mM, respectively), using an orbital shaker at 130 rpm, considering the conditions of 25 ºC temperature and darkness. The statistical software SPSS v.15.0 was used for the analysis of variance and comparison of means. The results showed the existence of significant differences between the treatments. Therefore, it is concluded that concentrations higher than 25 mM NaCl are harmful to pepper cultivation, and it is recommended to develop new varieties resistant to salinity in the face of the inclement weather of climate change. © 2025 Instituto de Botanica del Nordeste. All rights reserved.